AN ANALYSIS OF SPEECH ACTS IN THE STUDENT’S TEXTBOOK AT THE SENIOR VOCATIONAL HIGH SCHOOL - Sukmayanthi, Ni Made Ika; Tantra, Dewa Komang; Santosa, Made Hery (Universitas Pendidikan Ganesha, 2021)
The current research objectives were to analyse the eleventh grade students’ textbook in the Senior Vocational High School publishes by the Indonesian Ministry of National Education based on the 2013 Curriculum. The research problems were focused on the speech acts’ social functions, linguistic features, and language elements. The research was designed in a qualitative approach. Data were collected through document analysis method. Data were analysed descriptively by classifying the speech acts’ social functions, linguistic features, and language elements. The research was delimited on the verbal acts or speech acts, focusing on their social functions, linguistic structures, and language features as outlined in the 2013 Curriculum (Kemdikbud 2016). The three verbal learning focus assisted students in improving their communicative competence in English. The research findings are, firstly, there were four speech act types found, namely directive, assertive, expressive, and commissive acts. The speech acts’ social functions were ordering, asking, telling, advising, praying, stating, explaining, welcoming, thanking, apologizing, offering and refusing. Secondly, the speech acts’ linguistic features designed were imperative, interrogative, and declarative sentences. Thirdly, the speech acts’ language elements specifically grammatical rules used were simple present tense, simple past tense, present continuous tense, present perfect tense, and past continuous tense.